Psychological Content Parameters of Professionally Significant Qualities of Future Managers in the Field of Education - Rakhymberdiyeva, Ainur; Kariyev, Adlet; Aganina, Kundyz; Orazbayeva, Fauziya; Makhmetova, Saule (Journal of Education Culture and Society, 2025)
Aim. The aim of the research is to study the psychological content parameters of professionally significant qualities of future managers in the field of education.Methods. The research sample comprised 124 people aged 19 to 35, including males (n = 62; 50.00%) and females (n = 62; 50.00%). At the time of confirmative empirical research, the respondents were pursuing a degree at higher education institutions in Kazakhstan. All the research participants were studying management in the field of education. The following methods were applied: “Questionnaire of the Style of Self-Regulatory Behaviour” Varvara Morosanova (1991), “Motivation of Professional Activity” (Rean et al., 2006), “Diagnostics of the Individual’s Motivation Structure” V. Milman (1990), “Diagnostics of Personal Creativity” (Tunik, 2013), “Questionnaire for Diagnosing Personal Symptom Complex of Responsibility” (Kocharyan, 2011), and “Methodology for Studying the Level of Assertiveness” (Kappony & Novak, 1995).Results. Seventeen statistically significant correlations were established, ten correlations being direct and seven correlations being inverse. It was found that planning is the most dependent and essential style of self-regulatory behaviour. It was established that assessing outcomes has the highest level of autonomy. There was a caveat that high autonomy of the style “assessing outcomes” poses a latent danger. The Student’s t-test allowed us to find out that the parameters of cognitive, motivational, operational, personal, and communicative components have a statistical superiority in the levels of the styles of self-regulatory behaviour. It was substantiated that the motivational component is important in planning and modelling. It was established that the parameter self-affirmation has the largest number of superiorities in the styles of future managers’ self-regulatory behaviour.Conclusions. Future managers prefer planning, modelling and assessing outcomes styles of self-regulatory behaviour. The obtained results should be implemented in training future managers in the field of education.